How green is your supply chain? Evidence from ISO 14001 certified manufacturers in Malaysia - Rusli, Khairul Anuar; Abd Rahman, Azmawani; Ho, Jo Ann; Abdullah, Rashid (Universiti Putra Malaysia Press, 2013)
Extraordinary current consumption in the developed countries as well as in the Asian region, as a result of rapid industrialization, has increased the levels of energy and material consumption. This has posed negative consequences on the natural resources and the environment. The question of how to make economic and infrastructure growth environmentally and socially sustainable, so that it can continue to benefits people while conserving the natural assets and ecosystem continues to challenge policy makers, industry, and consumers. This research investigates the level of green supply chain management (GSCM) practices adopted by ISO 14001 certified manufacturers in Malaysia. Based on the data collected through the questionnaire survey, it was found that most manufacturers have not yet fully adopted the green practices within their supply chain activities. Only 17 percent of the total respondents were proactive adopters of the GSCM practices. The internal environmental practices have been found to be the top GSCM practices, followed by eco-design and investment recovery. The least common GSCM practice is reverse logistics. The study offers implications to both theory and practice.